Diversi Penyidik Dalam Penyelesaian Perkara Pidana Anak Melalui Restorative Justice - Tarantung, Yosep; Sudarmanto, Kukuh; Sihotang, Amri Panahatan; Sukarna, Kadi (Universitas Semarang, 2023)
The purpose of this research is to analyze the investigation of juvenile criminal cases through restorative justice in the Central Java Regional Police (Polda Jawa Tengah). The importance of a friendly and fair resolution for children facing the law. The diversion of cases from the criminal justice process to non-criminal justice processes. Diversion can be carried out when the criminal threat is below 7 (seven) years and is not a repeat offense. This type of research uses a socio-legal approach. The research findings indicate that the juvenile diversion process in Central Java Regional Police involves transferring cases from the criminal court to a deliberation process to achieve balance and restoration. Mediators in the deliberation can be trusted community figures, school principals, or teachers. Standard rules are needed for non-formal treatment of cases involving children in conflict with the law to limit negative practices in the justice system. Diversion is carried out to promote the well-being of children, especially in cases of juvenile delinquency, and to prevent recidivism. Tujuan penelitian ini untuk menganalisis penyidikan terhadap perkara tindak pidana anak melalui restorative justice di Polda Jawa Tengah. Pentingnya penyelesaian perkara yang ramah dan adil bagi anak yang berhadapan dengan hukum. Pengalihan perkara dari proses peradilan pidana ke proses di luar peradilan pidana. Diversi dapat dilaksanakan apabila ancaman pidananya di bawah 7 (tujuh) tahun; dan bukan merupakan pengulangan tindak pidana. Jenis penelitian ini menggunakan yuridis sosiologis. Hasil penelitian proses diversi anak pada Polda Jawa Tengah melibatkan pengalihan perkara dari pengadilan pidana ke proses musyawarah untuk mencapai keseimbangan dan memulihkan keadaan. Mediator dalam musyawarah dapat berupa tokoh masyarakat yang dipercaya atau kepala sekolah atau guru. Aturan standar diperlukan untuk perlakuan non-formal terhadap kasus anak yang berkonflik dengan hukum untuk membatasi praktik negatif dalam sistem peradilan. Diversi dilakukan untuk mencapai kesejahteraan bagi anak, khususnya terhadap kejahatan anak, dan untuk mencegah terjadinya residivis.